Advances in the use of synthons in organic chemistry : a research annual. - Dondoni, Alessandro (Jai Press, 1993)
Advances in the Use of Synthons in Organic Chemistry: A Research Annual, Volume 1 provides information pertinent to a useful reagent that can perform a certain chemical operation that is otherwise impossible or difficult to carry out. This book presents the developments on established synthons.Organized into four chapters, this volume begins with an overview of the significant role of the formyl group in synthetic methodologies, which has stimulated the search for other reagents. This text then describes trimethysilyldiazomethane as a stable and safe substitute for hazardous diazomethane. Othe.